The city of Tijuana as seen by the residents of Fort Irwin, California (National Administration Journal, 2021)
The objective is to analyze the perception that the residents of Fort Irwin have about the city of Tijuana. For this quantitative methodology, a survey was applied to 260 inhabitants of Fort Irwin, and the instrument consists of four dimensions: general data, characteristics, services and perception of Tijuana. Results: the elements that motivate the citizens of Fort Irwin to visit Tijuana are the weather, the variety of cultural and outdoor activities and gastronomy but the negative aspects are the insecurity and lack of cleanliness in the city. Conclusion: the factors of safety, public services and gastronomy are those that are related in greater incidence with the image of the city of Tijuana.
Keywords: Image of the city; tijuana; fort irwin; tourism